A brief interactive training for health care professionals working with people affected by "female genital mutilation": initial pilot evaluation with psychosexual therapists. Issue 1 (2nd January 2016) - Elliott, Charmaine; Creighton, Sarah M.; Barker, Meg-John; Liao, Lih-Mei
ABSTRACT: The aim of the study was to evaluate a 90-minute professional training and education workshop on working with women affected by "female genital mutilation" (FGM). Forty-nine psychosexual therapists attended the workshop and completed the same questionnaire eliciting FGM knowledge and attitudes at the beginning and end of the workshop. Pre- and post-differences in responses to the questionnaire were taken to be the effect of the workshop intervention. Participant satisfaction was independently obtained by the conference organisers. Participants' knowledge of FGM improved significantly following the workshop. Post-workshop, more participants were able to identify the year FGM was made illegal ( X 2 (5, N = 97) = 32.36, p < .001), the classification of FGM ( X 2 (6, N = 97) = 29.10, p < .001) and UK prevalence data ( X 2 (6, N = 97) = 29.10, p < .001). Participants also identified significantly more practising communities ( t = 4.6, p < 0.001) and illegal cutting procedures ( t = 2.9, p = 0.004). Regarding shifts in attitude following the intervention, the participants expressed greater disagreement with circumcision on consenting adult males ( U = 806.5, p = 0.046 (one-tailed), r = 0.18). This suggests that a 90-minute interactive group workshop could be highly acceptable to recipients and enhance knowledge about FGM.